Farm structures and environment: The indispensable but unappreciated specialization of agricultural engineering in Nigeria. (2011)
Farm structures, a vital component of agricultural engineering is given very little recognition because of conflicts and ignorance. Neglected in terms of man power and facilities, its numerous potentials for agricultural development remain untapped. Climate change and noise from increasing farm mechanization activities are becoming threats to agricultural practice and a challenge to the farm structures experts. To appropriately respond to these challenges, due attention need to be given to the theory and practice of the profession while collaboration and information exchange among the experts need to be strengthened.